Surgical removal of periapical cyst in the anterior region of the maxilla: case report (Research, Society and Development, 2021)
Odontogenic cysts constitute a group of diverse heterogeneous lesions. The etiology of the periapical cyst is related to the epithelium of the apex of a dental unit that has pulp necrosis. Conventional endodontic therapy is considered the first option for the treatment of periapical cysts, however, in case of failure, surgical therapy is necessary. The study reports the case of a patient with a periapical cyst, performing a literature review on the subject and emphasizing the importance of histopathological examination to confirm the diagnosis. This is a descriptive documentary research, where data collected from medical records and photos of the patient will be used. Female patient who attended the dental school clinic of a private institution in the interior of Bahia, referred by a dentist for extraction and removal of a lesion in the periapex. Surgical removal of the periapical cyst should be considered when conventional endodontic treatment fails. It is necessary to carry out a careful clinical examination and evaluation of radiographic exams so that the best therapy can be instituted, bearing in mind the importance of the histopathological exam to confirm the diagnosis.